Application of conjugate gradient method with cubic non-polynomial spline scheme for solving two-point boundary value problems - H. Justine; Jumat Sulaiman (Global Academy of Training & Research (GATR) Enterprise., 2016)
Objective - Conjugate Gradient (CG) method is used to solve two-point boundary value problems together with non-polynomial spline approach at cubic degree.